A survey of Intrusion Detection Systems for Wireless Sensor Networks. (24th February 2012) - Farooqi, Ashfaq Hussain; Khan, Farrukh Aslam
Wireless Sensor Networks (WSNs) are vulnerable to various kinds of security threats that can degrade the performance of the network and may cause the sensors to send wrong information to the sink. Key management, authentication and secure routing protocols cannot guarantee the required security for WSNs. Intrusion Detection System (IDS) provides a solution to this problem by analysing the network in order to detect abnormal behaviour of the sensor node(s). Researchers have proposed various approaches for detecting intrusions in WSNs during the past few years. In this survey, we classify these approaches into three categories and discuss them in detail.